Вычислить производную функции при заданном значении аргумента [latex]f(x)=(x-1) \sqrt{x^{2}-1 }, x=2[/latex]

Вычислить производную функции при заданном значении аргумента [latex]f(x)=(x-1) \sqrt{x^{2}-1 }, x=2[/latex]
Гость
Ответ(ы) на вопрос:
Гость
f'(x)=(x-1)'*[latex] \sqrt{x^{2} -1} +(x-1)( \sqrt{ x^{2} -1)'} = \sqrt{ x^{2} -1} + (x-1) \frac{2x}{2 \sqrt{ x^{2} -1} } } =[/latex][latex] \sqrt{ x^{2} -1} } + \frac{x(x-1)}{ \sqrt{ x^{2} -1} } = \frac{ x^{2} -1+ x^{2} -x}{ \sqrt{ x^{2} -1} } = \frac{2 x^{2} -x-1}{ \sqrt{ x^{2} -1} } = \frac{(2x+1)(x-1)}{ \sqrt{ x^{2} -1} } = \frac{(2x+1) \sqrt{x-1} }{ \sqrt{x+1} } [/latex] при х=2  =[latex] \frac{(2*2+1) \sqrt{2-1} }{ \sqrt{2+1} } = \frac{5 \sqrt{3} }{3} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы